CONTEXTUAL DETERMINANTS FOR COMMUNITY BASED LEARNING PROGRAMMES IN NURSING EDUCATION IN SOUTH AFRICA - Mthembu, S; Mtshali, N; Frantz, J (South African Journal of Higher Education, 2016)
Community-based learning (CBL) is one of the fastest growing reforms in health professions education. This article aimed to present the contextual determinants of CBL and describes the casual conditions that led nursing education institutions to incorporate CBL in their curricula. A grounded theory research design was adopted. Two university-based schools of nursing were purposively selected to participate in the study and there were 16 participants. Data analysis entailed three phases; open, axial and selective coding. The contextual circumstances contributing to the implementation of CBL emerged as the nature of the graduates produced from the traditional vs the new curriculum; transformation of higher education; transformation of the healthcare system and transformation of nursing education in South Africa. CBL has emerged as a political instrument that has influenced not only a change in the country’s health system but has responded to the needs of the South African population at large.